2011
DOI: 10.4103/0378-6323.84061
|View full text |Cite
|
Sign up to set email alerts
|

Skin tags, leptin, metabolic syndrome and change of the life style

Abstract: The results of this study suggested that the presence of both ST and hyperleptinaemia in patients with STs may be associated with high levels of triglycerides and low levels of HDL and this could suggest that changing the life style of patients with ST may have a beneficial role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
5
10
0
Order By: Relevance
“…This is an agreement with El Safoury et al ., (2011) who measured the association of the METs in patients with STs and found a significant association, 26/40 (65%) compared to the control group 2/40 (5%) ( P < 0.001)[23] and in agreement with Shaheen et al ., (2011) who found that 71% of patient with STs fulfilled the criteria of METs. [24]…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This is an agreement with El Safoury et al ., (2011) who measured the association of the METs in patients with STs and found a significant association, 26/40 (65%) compared to the control group 2/40 (5%) ( P < 0.001)[23] and in agreement with Shaheen et al ., (2011) who found that 71% of patient with STs fulfilled the criteria of METs. [24]…”
Section: Discussionsupporting
confidence: 80%
“…A higher statistical significant difference in BMI was found in the cardiac-STs and non-cardiac-STs groups than in the control group ( P < 0.001). This is an agreement with Sari et al ., (2010)[21] who found that mean BMI was (29.9 ± 5.3) in the STs group and (21.5 ± 3.5) in the control group ( P < 0.001), with El Safoury et al .,[23] who found that BMI mean was 35.2 ± 7.05 in the STs group and 28.03 ± 4.29 in the control group ( P < 0.001), with Shaheen et al .,[24] who found that the number and extent of STs increased with the increase in obesity, with the results of Puneet and Deepak.,[27] who reported an association between STs, impaired glucose tolerance, and obesity, and finally with the results of Garcia-Hidalgo et al .,[28] who studied 156 obese patients and found that percentage of those with STs increased with severity of obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional evidence was provided by El Safoury et al, [29], who showed that the presence of both ST and hyperleptinemia may be associated with high levels of triglycerides and low levels of HDL-C.…”
Section: Discussionmentioning
confidence: 88%